Model-based estimates of sex differences in peak power and fatigue index in track cyclists using directed acyclic graphs, inverse probability of treatment weighting, and Bayesian modeling - Chavarro, J. G.; Gómez García, M. Á.; Bermeo, R. N. Z. (Frontiers in Physiology, 2026)
Objective: The purpose of this study was to estimate sex-related differences in peak power and fatigue index in track cyclists under an explicit causal modeling framework integrating directed acyclic graphs, inverse probability of treatment weighting, and hierarchical Bayesian estimation.